THU0438 Lack of predictive value of the NIAID/FAAN criteria to identify subjects with evidence of immune activation after receiving pegloticase for chronic refractory gout. (15th June 2017) - Calabrese, L; Kavanaugh, A; Yeo, A; Lipsky, P
Abstract : Background: The NIAID/FAAN criteria have been widely applied to identify anaphylaxis despite having only modest specificity.1, 2 Objectives: To evaluate the predictive value of the NIAID/FAAN criteria to identify evidence of immune activation in subjects with chronic refractory gout treated with pegloticase in randomized clinical trials (RCTS) who experienced infusion reactions (IRs), by assessing the capacity of biochemical testing for immunologic activation to confirm the likelihood of anaphylaxis. Methods: During the RCTs supporting the approval of pegloticase for treatment of chronic refractory gout, subjects remained on therapy despite becoming nonresponders, which reflected the development of anti-drug antibodies (ADA); ∼60% of subjects continued to receive pegloticase despite elevated ADA titers and many had IRs. In subjects receiving pegloticase every 2 weeks (q2w), 22/85 (25.9%) had a total of 43 IRs and 34/84 (40.5%) receiving pegloticase every 4 weeks (q4w) had a total of 70 IRs. 21/22 (95.5%) and 29/34 (85.3%) subjects with IRs in the q2w and q4w groups, respectively, were nonresponders. The 113 total IRs were categorized post hoc as to whether they met NIAID/FAAN criteria for anaphylaxis. Six IRs in 6 subjects met criteria, 53 IRs in 33 subjects had only one feature and were designated as "hypersensitivity", and 54 IRs in 29 subjects had no features and were designated "other". The clinical courses of these IRs and whether they were associated with elevated tryptase levels as a measure of mast cell degranulation or complement consumption as a measure of immune complex activity were assessed. Results: Of a total of 852 infusions in subjects receiving q2w pegloticase, 43 (5.0%) were associated with IRs as were 70 of 830 infusions (9.5%) in subjects receiving q4w pegloticase. Of the 70 IRs associated with q4w administration, 3 (4.3%) met the criteria for anaphylaxis, 31 (44.3%) for hypersensitivity and 36 (51.4%) were other. The respective values for subjects receiving pegloticase q2w were 3/43 (7.0%), 22/43 (51.1%), and 18/43 (41.9%). A total of 14 IRs (12.4%) were associated with elevated tryptase and 31 (27.4%) with decreased complement CH50 levels. Immunologic abnormalities were not significantly different in the 3 groups, with 16.7%, 17.0% and 7.4% of anaphylaxis, hypersensitivity and other IRs, respectively, having increased tryptase; and 0%, 30.2%%, and 27.8%, respectively, having decreased complement. No subjects were classified as experiencing anaphylaxis by investigators, none required hospitalization, and 60.7%, continued to receive pegloticase. Conclusions: Post-hoc designation of pegloticase-treated subjects as meeting NIAID/FAAN criteria for anaphylaxis was not associated with a higher frequency of biochemical evidence of immune activation or a more severe clinical course. In pegloticase-treated subjects, the NIAID/FAAN anaphylaxis criteria did not identify subjects with IRs associated with elevated tryptase and decreased complement CH50 levels. References: Sampson HA, et al. J Allergy Clin Immunol. 2006;117:391–397. Campbell RL, et al. J Allergy Clin Immunol. 2012;129:748–752. Disclosure of Interest: L. Calabrese Consultant for: BMS, Genentech, Horizon, Crescendo, Pfizer, GSK, Regeneron, UCB, Abbvie, Janssen, A. Kavanaugh Consultant for: Abbvie, Amgen, Janssen, BMS, UCB, Pfizer, A. Yeo Consultant for: Horizon Pharma, P. Lipsky Consultant for: AstraZeneca, Celgene, EMD Serono, GSK, Horizon Pharma, Janssen, Medimmune, Pfizer, Roche, Sanofi, UCB